Body mass index and serum lipid profile: Association with atopic dermatitis in a paediatric population. (10th September 2019) - Agón‐Banzo, Pedro Jesús; Sanmartin, Rosalía; García‐Malinis, Ana Julia; Hernández‐Martín, Ángela; Puzo, José; Doste, Divina; Pardos, Carlos; Gilaberte, Yolanda
Abstract: Background/Objectives: The association between atopic dermatitis, body weight and serum lipid levels is not well known, and very few studies have examined this relationship in children. Methods: Children ( n  = 239) under 14 years old participated in this prospective cross‐sectional study. The following variables were recorded: age, gender, weight, height, atopic dermatitis severity, serum levels of total cholesterol, low‐density lipoprotein cholesterol, high‐density lipoprotein cholesterol and triglycerides. Results: Mean body mass index was slightly higher in atopic dermatitis patients than healthy controls and significantly higher in atopic dermatitis patients aged 0–2 years (atopic dermatitis, 16.7 ± 4.6; controls, 15.7 ± 1.3; P  = 0.04) and 12–14 years (atopic dermatitis, 24.9 ± 5.3; controls, 20.6 ± 3.4; P  = 0.03). Among atopic dermatitis patients, body mass index was significantly higher in those with severe atopic dermatitis in the 9–12 ( P  = 0.03) and 12–14 ( P  = 0.01) years groups. Mean serum lipid levels were higher in patients with severe atopic dermatitis than in the atopic dermatitis group as a whole. These differences reached statistical significance for total cholesterol ( P  = 0.04) and triglycerides ( P  = 0.02). Conclusion: The prevalence of overweight, obesity and dyslipidemia is greater in children with atopic dermatitis than in age‐matched healthy counterparts.